PREFERENSI WISATAWAN TERHADAP KUNJUNGAN WISATA DI KUSUMA AGROWISATA KOTA BATU JAWA TIMUR - Ginantius, ardaniel (Berkala Ilmiah AGRIDEVINA, 2019)
Based on the results of analysis, the first objective of consumer characteristics in Kusuma Agrowisata is dominated by male gender with adult age of 25-35 Years. Background The dominant education of SMA and Diploma with employment as private and entrepreneur employee who have income Rp.2.500.000, - Rp. 5.000.000.-. The area of ​​origin of visitors or tourists dominated local area of ​​East Java. Where the factors influencing the tourist visit in kusuma agrowisata based on simultaneous test (Test F) that attraction, facility, additional service, accessibility, security, and promotion together (simultaneously) have a positive effect to visit wisata at Kusuma Agrowisata Kota Batu . While partially (t test): The influence of Attraction, Facility, Accessibility, Security and Promotion have a positive effect on tourist visit. For Additional Services negatively affect tourist visits. DOI : https://doi.org/10.33005/adv.v8i1.1626